2020
DOI: 10.20537/2076-7633-2020-12-1-59-72
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the natural convection of a non-Newtonian fluid in a closed cavity

Abstract: In this paper, a time-dependent natural convective heat transfer in a closed square cavity filled with non-Newtonian fluid was considered in the presence of an isothermal energy source located on the lower wall of the region under consideration. The vertical boundaries were kept at constant low temperature, while the horizontal walls were completely insulated. The behavior of a non-Newtonian fluid was described by the Ostwald de Ville power law. The process under study was described by transient partial differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…But in non-Newtonian fluids, the amount of fluid viscosity depends on the force applied to that fluid. In Newtonian fluids, the relationship between stress and strain rate is linear, but in non-Newtonian fluids, this relationship is nonlinear, and in this range of fluids, the duration of stress plays an important role in the resulting shear stress [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But in non-Newtonian fluids, the amount of fluid viscosity depends on the force applied to that fluid. In Newtonian fluids, the relationship between stress and strain rate is linear, but in non-Newtonian fluids, this relationship is nonlinear, and in this range of fluids, the duration of stress plays an important role in the resulting shear stress [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effect of applying a magnetic field on the rate of heat transfer was greater for Hartmann numbers less than 30. Loenko et al [27] investigated heat transfer of non-Newtonian and Newtonian fluids in a square chamber with a heat-generating barrier. The results showed that increasing the fluid power-law fluid index led to reducing the fluid velocity and a faster stationary mode was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have been performed to consider computational techniques for different models for different approaches, it is essential to improve the past research on computational methods (Mahian et al , 2019; Dogonchi et al , 2018; Izadi et al , 2018; Sheremet et al , 2018; Sheremet et al , 2017; Ellahi et al , 2016; Pop et al , 2016; Dinarvand et al , 2016; Bondareva et al , 2015; Dinarvand et al , 2015; Izadi et al , 2020; Miroshnichenko et al , 2020; Bondareva et al , 2020; Loenko and Sheremet, 2020; Sheremet et al , 2019; Astanina et al , 2019; Gibanov and Sheremet, 2019; Miroshnichenko et al , 2018; Sheremet et al , 2018; Bondareva et al , 2018; Chamkha et al , 2020; Mehryan et al , 2020; Krishna et al , 2020; Mansoury et al , 2020; Sadeghi et al , 2020; Dogonchi et al , 2020; Ghalambaz et al , 2020; Ishak et al , 2020; Rejvani et al , 2019; Alsabery et al , 2019; Mehryan et al , 2019; Hoseinzadeh et al , 2019; Taamneh et al , 2019; Raza et al , 2019). The overall strategy considered in this study was to couple the LES with the BMH soot model through a non-premixed flamelet combustion model for the study of soot evolution process in a diffusion flame for three different configurations at an average stain rate of 4,100 (s −1 ) to understand soot dynamics study such as SVF and the various stages of soot formation such as soot nucleation rate, coagulation rate, soot surface oxidation rate and soot surface growth rate.…”
Section: Introductionmentioning
confidence: 99%